Effect of Food Waste Co‐Digestion on Digestion, Dewatering, and Cake Quality. (1st January 2017) - Higgins, Matthew; Rajagopalan, Ganesh; Miller, Andre; Brown, Jeffrey; Beightol, Steven
ABSTRACT: : The objective of this study was to evaluate the effect of food waste addition on anaerobic digestion performance as well as downstream parameters including dewatering, cake quality, and filtrate quality. Laboratory‐scale digesters were fed processed food waste at rates of 25%, 45%, and 65% increased chemical oxygen demand (COD) loading rates compared to a control fed only primary and secondary solids. The specific methane yield increased from 370 L CH4 /kg VSadded for the control to 410, 440, and 470 L CH4 /kg VSadded for the 25, 45, and 65% food waste addition, respectively. The cake solids after dewatering were all higher for the food waste digesters compared to the control, with the highest cake solids being measured for the 45% food‐waste loading. Compared to the control digester, the biosolids odorant concentration increased for the lowest dose of food waste. Odorant concentrations were below detection for the highest food waste loading.